Traumatic Intraconal Foreign Body: Report of an Injury Corrected With Combined Surgical and Endoscopic Treatment. Issue 1 (March 2016) - Marchioni, Daniele; Bertossi, Dario; Soloperto, Davide; Bianconi, Luca; Procacci, Pasquale; Nocini, Pier Francesco
Abstract : BACKGROUND: Management of penetrating ocular splinter injuries is very controversial. Penetrating wounds of the orbit represent a complex therapeutic problem that requires a multidisciplinary approach. Endoscopic approaches to the orbit are currently performed through the lamina papyracea to access the medial part, or through large orbitotomies to access the lateral part. OBJECTIVE: To describe a novel combined approach to the lateral part of the orbit. METHODS: Clinical and surgical findings of intraorbital foreign body removal are presented. A minimal supraorbital osteotomy was performed, combined with endoscopic intraorbital dissection. RESULTS: The foreign body was removed, no postoperative complications were reported, and visual acuity increased from 2/10 preoperatively, to 8/10 one month after surgery. CONCLUSION: The present technique can be considered a safe and novel surgical approach to access the retrobulbar space and to treat the pathology of this anatomic region.